2021
DOI: 10.2147/opth.s305520
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Foveal Avascular Zone in Familial Exudative Vitreoretinopathy Using Optical Coherence Tomography Angiography

Abstract: Purpose To evaluate the foveal avascular zone (FAZ) and retinal structure in familial exudative vitreoretinopathy (FEVR). Patients and Methods Eighteen eyes with stage 1 or 2 FEVR and 20 control eyes were evaluated. The central retinal thickness (CRT), foveal inner retinal thickness (IRT), surface retinal vessel density (SRVD), and deep retinal vessel density (DRVD) were measured using optical coherence tomography. The FAZ area was calculated using ImageJ software. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Greater foveal thickness and central macular thickness; microstructural change, including posterior hyaloidal disorganization; vitreomacular traction; macular edema; and EZ disruption are correlated with poorer visual acuity in stage 1 and stage 2 FEVR [ 64 ]. A thicker central retinal thickness (CRT) can be attributed to a residual retinal inner layer and the absence of a foveal pit [ 71 , 72 ]. A recent publication by Zhang et al described using ultra-wide-field laser ophthalmoscopy and optical coherence tomography to identify a novel sign of temporal mid-peripheral vitreoretinal interface abnormality (TEMPVIA) in early-stage FEVR, which was characterized by retinal thickening at the posterior margin of avascularized retina, with mild or absent retinoschisis and leakage on the FA [ 73 ].…”
Section: Oct and Octa In Retinal Vascular Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Greater foveal thickness and central macular thickness; microstructural change, including posterior hyaloidal disorganization; vitreomacular traction; macular edema; and EZ disruption are correlated with poorer visual acuity in stage 1 and stage 2 FEVR [ 64 ]. A thicker central retinal thickness (CRT) can be attributed to a residual retinal inner layer and the absence of a foveal pit [ 71 , 72 ]. A recent publication by Zhang et al described using ultra-wide-field laser ophthalmoscopy and optical coherence tomography to identify a novel sign of temporal mid-peripheral vitreoretinal interface abnormality (TEMPVIA) in early-stage FEVR, which was characterized by retinal thickening at the posterior margin of avascularized retina, with mild or absent retinoschisis and leakage on the FA [ 73 ].…”
Section: Oct and Octa In Retinal Vascular Diseasesmentioning
confidence: 99%
“…Conventional FA imaging of FEVR was able to show peripheral avascularized areas, abnormal venous–venous anastamosis, vascular branching and leakage in the peripheral retina [ 73 ]. In terms of OCTA of FEVR, central macular microvascular change was noted in several studies, which suggested that there may be more to FEVR than peripheral retinal avascularization [ 67 , 71 , 72 ]. Hsu et al reported a series of 11 eyes of 6 patients with FEVR imaged with OCTA, which showed dilation, disorganization, straightening, heterogeneous vessel density and curls formation in SCP [ 67 ].…”
Section: Oct and Octa In Retinal Vascular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation